Plasma profiles, self-organization and alfven eigenmodes studies using the HIBP diagnostic in the TJ-II stellarator - Krupnik, L.I.; Barcala, J.M.; Cappa, A.; Chmyga, O.O.; Dreval, M.B.; Hidalgo, C.; Khrebtov, S.M.; Komarov, O.D.; Kozachok, O.S.; Martínez, J.; Molinero, A.; Pablos, J.L. (Problems of Atomic Science and Technology, 2023)
This paper reports recent experiments in the TJ-II stellarator using a dual Heavy Ion Beam probe diagnostic. The studies were focused on characterizing plasma potential profiles, investigating self-organization mechanisms and Alfven Eigenmodes (AEs). Results showed plasma equipotential measurements consistent with vacuum magnetic surfaces and the presence of zonal flows in the plasma core region. The investigation of Alfven Eigen modes showed their radial localization and poloidal asymmetries in potential and density fluctuations driven by AEs. Повідомляється про нещодавні експерименти на стелараторі TJ-II з використанням подвійної діагностики на пучках важких іонів. Дослідження були зосереджені на характеристиках профілів потенціалу плазми. Досліджено механізми самоорганізації та власних мод Альфвена (AE). Результати показали, що вимірювання еквіпотенціалу плазми відповідають вакуумним магнітним поверхням і наявності зональних потоків в області плазмового ядра. Дослідження власних мод Альфвена показало їх радіальну локалізацію та полоїдальну асиметрію у коливаннях потенціалу та густини, викликаних AE.